Multi-Dimensional Student's Result Analytical Processing For Tertiary Institutions (International Journal of Engineering and Computer Science, 2018)
The objective of this paper work is to develop a web based analytical processing of students’ record in a tertiary institution which will accept student data at all levels, determine students’ performance over a period of time, extract specific information available from the database when there is need and improve the privacy, user-friendliness and enable convenient access to students’ information mounted on the portal. This is done in other to determine the quality of students being graduated over time from the institution. our motivation was bourne out of the need to reduce the stress and discomfort departments encounter during  students reconciliation of result. This will help in obtaining accurate information. It will also reduce bribery whereby people with money gets faster attention than others. In other to mine the database of students’ results, the Structured System Analysis and design approach to software engineering was used in the course of this work. This involves identifying the problem which involved looking at the students’ results for area of weaknesses and designing how to go about this identification, acquisition of knowledge and problem solving strategies. The data were collected majorly by interviews and observation. The result generated will help the staff (Lecturers) of the department to remotely input and monitor their results without stress after it has been approved by the senate of the Institution. The department can also have a quick view of student’s record and make a quick decision on it.